Modelo de redacción escalonada para el desarrollo de la escritura académica - Loayza-Maturrano, Edward Faustino (2025)
The objective of the research was to determine the influence of the staggered writing strategy (summary, comment and essay) from the intertextuality approach, in the development of academic writing competence in university students. The methodology was qualitative of phenomenological-hermeneutical design because it involved two stages: the application of the strategy and the evaluation of the writing portfolio. The convenience sampling of several groups of students enrolled in the Technical Writing course at a public university was considered. The results show a higher academic writing competence in the experimental group. The students stood out for showing better argumentative writing, greater length of writing, fewer lexical-grammatical errors. The main conclusion of the research is that the influence of the staggered writing strategy significantly influences the development of academic writing competence in university students.